2022
DOI: 10.1108/ijssp-06-2022-0170
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived organizational support on professional commitment: a moderation of burnout and mediation of well-being

Abstract: PurposeIn today’s challenging world, achieving professional commitment among healthcare workers is becoming the need of time. Drawing on self-determination theory, the current study examines how and under which boundary conditions perceived organizational support affects professional commitment.Design/methodology/approachData was collected from doctors and nurses employed in public and private sector hospitals by employing a split-questionnaire design.FindingsThe authors’ study findings demonstrate that percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Thirdly, perceived organisational support can also enhance the commitment of banking industry managers in post-merger decisions. This finding is in line with Ilyas et al ’s (2022) finding. Organisational commitment has contributed to the organisation’s success in promoting and convincing potential customers of Fintech products and services that comply with Shariah guidance.…”
Section: Discussion and Implicationsupporting
confidence: 93%
See 1 more Smart Citation
“…Thirdly, perceived organisational support can also enhance the commitment of banking industry managers in post-merger decisions. This finding is in line with Ilyas et al ’s (2022) finding. Organisational commitment has contributed to the organisation’s success in promoting and convincing potential customers of Fintech products and services that comply with Shariah guidance.…”
Section: Discussion and Implicationsupporting
confidence: 93%
“…Organisational commitment reflected employee participation and willingness to be part of the organisation (Chaudhary et al , 2023). Further, perceived situational support could improve organisational commitment (Ilyas et al , 2022). Adiwijaya and Hayati (2023) found that organisational commitment significantly influenced readiness to change in the Central Bureau of Statistics organisation.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the construct comprehensively, professional well-being in organizational studies has frequently extracted common items (e.g., a creative organization really cares about motivation, achievement, work productivity, and performance) [ 52 , 55 ]. Meanwhile, the latter constructs the professional well-being scale of employees (e.g., I definitely want a career for myself in organizational work outcomes) [ 56 ]. For example, Eatough et al [ 57 ] developed the main constructs of professional well-being based on self-esteem in organizing employees (e.g., at the moment, I feel that I have a number of good qualities).…”
Section: Context and Theoretical Constructsmentioning
confidence: 99%
“…Consequently, hospitals' staff not only had to work at the limit during the COVID-19 pandemic-that still persists-but might continue in the emergency status in the near future. This situation shows the need for scholars to focus their attention on the wellbeing of health personnel as a priority issue to address (Qaiser and Abid, 2022;Ilyas et al, 2022aIlyas et al, , 2022b. In the healthcare setting, employees' wellbeing acquired special relevance due to its relationship with performance.…”
Section: Introductionmentioning
confidence: 99%
“…During the heavy burden due of the pandemic, the primary purpose of the caring profession and healthcare organizations was to save patients' life by continuously enhancing their wellbeing (De Kock et al, 2021;Ilyas et al, 2022aIlyas et al, , 2022b. However, not only do the patients require attention, but the health staff also needs it.…”
Section: Introductionmentioning
confidence: 99%